An Investigation of Adolescents' Social Media Use and Self-Perceptions in the Framework of Peer Bullying - Kaplan, Veysel; Düken, Mehmet Emin; Kaçkin, Özlem; Almazan, Joseph (Utan Kayu Publishing, 2023)
The study aims to examine the effect of peer bullying that adolescents are exposed to on their self-perceptions and social media use. The present study that included 198 participants was planned descriptive, relational and cross-sectional. In addition to the personal information form, Adolescent Social Media Use Scale, Child-Adolescent Bullying Scale-9 Short Form and Social Comparison Scale were used to collect the data. SPPS 22.0 package program was used in the analysis of the data. Descriptive data of the research are given with mean and frequency. To analyse the data One-Way ANOVA, t-test, and Bivariate Correlation were used. The mean age of the adolescents included in the study was determined as 15.32 ± 1.03. It was determined that 50% of the participants were men, 79.8% were living in nuclear families and 17.2% were individuals who felt psychologically bad. Besides, it was revealed that the mean score of the adolescents' self-perception scale was 81.96 ± 14.3, the mean score of peer bullying was 19.46 ± 8.39, and the mean score of the adolescent social media scale use was 18.15 ± 6.68. As a result of the analyzes, it was determined that there is a strong and significant relationship between the adolescents' exposure to peer bullying, their self-perceptions, and their use of social media. It has been determined that exposure to peer bullying negatively affects adolescents' self-perceptions and may cause addiction to social media use.